Fundamentals of CRM with Dynamics 365 and Power Platform Enhance Your Customer Relationship Management by Extending Dynamics 365 Using a No-Code Approach. - Tarla, Nicolae (Packt Publishing, Limited, 2020)
Fundamentals of CRM with Microsoft Dynamics 365 and Power Platform is a practical guide that will take you through all the essential components of Dynamics 365. This book will show you how Dynamics 365 leverages and extends the Power Platform capabilities to build effective business solutions customized to meet your organization's needs.